Budaya Organisasi Pada Dinas Kesehatan Kabupaten Sumedang - Edi Setiawan (Jurnal Manajemen Pelayanan Publik, 2018)
Abstract. The purpose of this research is to determine the data’s description and the causal factor of the weak of Organizational Culture At The Health Department In Kabupaten Sumedang. This research used a quantitative method. In order to acquire the data that is necessary, the researcher has been conducting an interview with 15 informant and then the data is being processed by a data collection method; primary data which is include: Observation, Interview, Documentation. The data that has been collected then being processed refers to a data analysis technique by Miles and Huberman Model which is: Reduction Data, Display Data, Conclusion Drawing/Verification, Triangulation. According to the result of the research can be concluded that weak of organizational culture of Health Department at Kabupaten Sumedang is caused by the people’s awareness to live healthy is still low. There are some employee that always have to be guided continuosly about how to do their work, where some employee only rutinized only. The Department Head is more focus to a certain technical things, and also the agresiveness dan competitive of the employee on working is still low. To actualized a strong organizational cultural according to the 3 main elements above, it’s necessary an appraisal and reward for an innovated employee, people empowerment to live healthy, employee development, the department head can be more result-oriented, job enrichment in such a way which is can make employee become more aggressive and competitive.